Final Results of a Phase 2 Multi‐Arm Study of Magrolimab Combinations in Patients With Relapsed/Refractory Multiple Myeloma - Barry Paul; Jiri Minarik; Francesca Cottini; Cristina Gasparetto; Jack Khouri; Mitul Gandhi; Jens Hillengass; Moshe Levy; Michaela Liedtke; Sudhir Manda; Irwindeep Sandhu; Douglas Sborov; et al. (eJHaem)
Abstract Introduction Patients with pretreated relapsed/refractory multiple myeloma (RRMM) have a poor prognosis and limited treatment options, underscoring the need for safe treatments with durable efficacy. Methods This Phase 2 study evaluated magrolimab (Magro) plus daratumumab (Dara) or pomalidomide/dexamethasone (Pd) or carfilzomib/dexamethasone (Kd) in RRMM. The primary efficacy endpoint was objective response rate (ORR). Results ORR was 14.3% (Magro+Dara; n = 14), 20.0% (Magro+Pd; n = 10) and 36.4% (Magro+Kd; n = 11). There were two dose‐limiting toxicities: febrile neutropenia (Magro+Dara) and infusion‐related reaction (Magro+Pd). Grade ≥ 3 Magro‐related adverse event (AE) rates were 64.3% (Magro+Dara), 60.0% (Magro+Pd) and 63.6% (Magro+Kd). Two deaths were AE‐related; neither was Magro related. Conclusion As the study closed early, insights into the clinical profile of Magro combinations in RRMM are limited. Trial Registration This trial was registered at www.clinicaltrials.gov as #NCT04892446